YI-4 Non invasive assessment of pulmonary capacitance in the fontan patient correlates with functional class and peak oxygen consumption. (2nd March 2016) - Luke, Louis; Rutter, Luke; Bowater, S; Hudsmith, L; Thorne, S; Clift, P
Abstract : Introduction: A low pulmonary vascular resistance is essential for the Fontan circulation. Direct measurement of pulmonary vascular resistance (PVR) is only possible at cardiac catheterisation. Pulmonary arterial capacitance inversely correlates with PVR and can be approximated non-invasively using data derived from a maximal cardiopulmonary exercise test (CPEX) 1 . We have determined the non-invasive pulmonary arterial capacitance (ventilatory product) in a large cohort of adult Fontan patients. Methods: Maximal cardiopulmonary exercise testing was performed using a Ramp protocol on a standard exercise treadmill with gas exchange determined by continuous monitoring using a metabolic cart (GE Medical). The following parameters were obtained: peak oxygen consumption (pVO2 ), oxygen pulse (O2 pulse), maximum workload, peak end tidal CO2 (pet CO2 ) and VE/VCO2 slope. Functional NYHA class was determined by review of the clinical records. Pulmonary arterial capacitance was derived from the product (O2 pulse x pet CO2 ) as previously described 1 . Mean ventilatory product was determined for each functional class (1, 2 and 3–4), correlation between ventilatory product and maximum workload and pVO2 was assessed using a Pearson correlation Results: 142 adult Fontan patients underwent CPEX. Average age 28 ± 9 years, 15 ± 4 years since Fontan surgery. Mean pVO2 23.6 ± 8.5 mls/kg/min. Mean ventilator product correlated positively with pVO2 (r 2 =0.63) and maximal workload (r 2 =0.74) and negatively with VE/VCO2 slope (r 2 = -0.52). When determined for each functional class ventilatory product was as follows: NYHA 1 360 ± 117, NYHA II 270 ± 109 NYHA III and IV 228 ± 93. Discussion: Invasive measurements of PVR are difficult in the Fontan patient. We have demonstrated that a non-invasive derived measurement of pulmonary arterial capacitance, the ventilatory product, closely correlates with measures of performance, negatively correlates with PetCO2 which is known to correlate with mean pulmonary artery pressure. Furthermore we have demonstrated that ventilatory product falls with increasing exercise intolerance. We propose that ventilatory product may be used to assess Fontan patients suitable for pulmonary vasodilator therapy. This hypothesis requires testing in prospective studies of pulmonary vasodilator therapy in Fontan patients. Reference: Taylor BJ, Olson TP, Chul-Ho-Kim, et al . Use of noninvasive gas exchange to track pulmonary vascular responses to exercise in heart failure. Clin Med Insights Circ Respir Pulm Med. 2013;7:53–60